2012
DOI: 10.1007/s13277-012-0590-1
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of SHP-2 is associated with less favorable prostate cancer outcomes

Abstract: Src homology 2 domain-containing tyrosine phosphatase-2 (SHP-2) is an important regulator of cell signaling because of its ability to dephosphorylate receptors of growth factors as well as the cytokines and tyrosine-phosphorylated proteins associated with these receptors. In the current study, we used four different prostate cancer cell lines: PC3, DU145, LNCaP and LNCaP-IL6+. Tumor specimens from 122 patients with prostate cancer were analyzed using a tissue microarray. Our data demonstrate that all four pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…GIV mRNA and protein increase during cancer progression (2,3,12)), and GIV is essential for tumor cell invasion and neoangiogenesis (3,4), whereas expression of SHP-1 is suppressed during cancer progression, and SHP-1 is known to inhibit angiogenesis (57)(58)(59)(60)(61)(62). Because the role of GIV-dependent PI3K-Akt enhancement and cell migration extends beyond tumor cell invasion/metastasis into other diverse biological processes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…GIV mRNA and protein increase during cancer progression (2,3,12)), and GIV is essential for tumor cell invasion and neoangiogenesis (3,4), whereas expression of SHP-1 is suppressed during cancer progression, and SHP-1 is known to inhibit angiogenesis (57)(58)(59)(60)(61)(62). Because the role of GIV-dependent PI3K-Akt enhancement and cell migration extends beyond tumor cell invasion/metastasis into other diverse biological processes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The radical prostatectomy cohort from Oslo University Hospital (RP1) included 115 patients laparoscopically operated at Aker University Hospital (presently Oslo University Hospital, Aker) in 2004. The RP2 cohort from Skåne University Hospital consists of 122 patients with localized prostate cancer operated in Malmö between 1998 and 2003, as described previously . In the androgen deprivation therapy (ADT) cohort, 61 patients treated with TUR‐P and ADT at Oslo University Hospital in the period 1992–2008 were identified retrospectively from medical records as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Alphelys). The construction of the TMA from Skåne University Hospital has been described previously . In short, areas representing malignant and benign tissues were marked on hematoxylin/eosin stained sections and two cores of 1.0 mm were transferred to a TMA block using a manual arraying device (MTA‐1 Beecher Instruments Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several conflicting reports on the association between Shp2 and cancer. Certain studies have found that the expression of Shp2 decreases in certain types of tumor (8)(9)(10). However, the opposite was concluded in hepatocellular carcinoma (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%